Selective estrogen receptor modulators differentially alter the immune response of gilthead seabream juveniles. (May 2016) - Rodenas, M.C.; Cabas, I.; García-Alcázar, A.; Meseguer, J.; Mulero, V.; García-Ayala, A.
Abstract: 17α-ethynylestradiol (EE2 ), a synthetic estrogen used in oral contraceptives and hormone replacement therapy, tamoxifen (Tmx), a selective estrogen-receptor modulator used in hormone replacement therapy, and G1, a G protein-coupled estrogen receptor (GPER) selective agonist, differentially increased the hepatic vitellogenin ( vtg ) gene expression and altered the immune response in adult gilthead seabream ( Sparus aurata L.) males. However, no information exists on the effects of these compounds on the immune response of juveniles. This study aims, for the first time, to investigate the effects of the dietary intake of EE2, Tmx or G1 on the immune response of gilthead seabream juveniles and the capacity of the immune system of the specimens to recover its functionality after ceasing exposures (recovery period). The specimens were immunized with hemocyanin in the presence of aluminium adjuvant 1 (group A) or 120 (group B) days after the treatments ceased (dpt). The results indicate that EE2 and Tmx, but not G1, differentially promoted a transient alteration in hepatic vtg gene expression. Although all three compounds did not affect the production of reactive oxygen intermediates, they inhibited the induction of interleukin-1β ( il1b ) gene expression after priming. Interestingly, although Tmx increased the percentage of IgM-positive cells in both head kidney and spleen during the recovery period, the antibody response of vaccinated fish varied depending on the compound used and when the immunization was administered. Taken together, our results suggest that these compounds differentially alter the capacity of fish to respond to infection during ontogeny and, more interestingly, that the adaptive immune response remained altered to an extent that depends on the compound. Highlights: EE2 and Tmx, but not G1, promote a transient endocrine disruption in gilthead seabream juveniles. EE2, Tmx and G1 promote a transient, but differential, alteration on the innate immune response. Only Tmx increases the number of IgM positive lymphocytes in juveniles. EE2, Tmx and G1 promote a persistent effect on the antibody response of juveniles.